Rediscovering Awe: A New Front in Humanistic Psychology, Psychotherapy, and Society - Schneider, Kirk J. (Canadian Journal of Counselling and Psychotherapy, 2008)
This article is adapted from an invited address to the university of Laval, Quebec City, on April 7, 2006. The purpose of the article is to describe an emerging psychospiritual paradigm that veers between dogmatic fundamentalism and postmodern nihilism. This “depth” spirituality is based on a rediscovery of our native capacity for awe, and addresses the very fulcrum of our contemporary lives. It is a spirituality informed by the existentialtheological tradition of Soren Kierkegaard, Paul Tillich, Ernest Becker, and Rollo May, which welds the zeal and exaltation for religion with the scrupulosity and skepticism of science. Drawing from my recent book Rediscovery of Awe: Splendor, Mystery, and the Fluid Center of Life (Schneider, 2004) as well as both film and literature, I explore the nature, power, and therapeutic implications of the spiritual capacity for awe.